Penerapan Prototyping dalam Perancangan Sistem Informasi Presensi Kepegawaian (Studi Kasus Pengelolaan Kehadiran Pegawai) - Ihsan Fatul Korib; Wahyu Krishantoro (Infotek: Jurnal Informatika dan Teknologi, 2026)
The rapid development of information technology encourages educational institutions to manage employee administration more effectively, particularly in recording staff attendance, which serves as a basis for evaluating discipline and performance. The manual attendance process that relies on physical logbooks and Excel-based recapitulation often leads to delays, input errors, and potential data loss. This study aims to design a web-based employee attendance information system as a more structured, accurate, and accessible solution. The research adopts a Research and Development (R&D) approach, which includes preliminary studies, data collection through observation, interviews, and literature review, as well as needs analysis to formulate a system design that aligns with the school’s operational conditions. The system design was developed using the Prototyping method, while process modeling and functional requirements were documented using UML as the basis for constructing the system workflow. The results of this study produce a system design that supports real-time attendance recording, integrates location validation and photo documentation, and provides automatically generated reports that can be printed or exported. This research contributes by offering a digital attendance system model that is more efficient, accurate, and adaptive to modern administrative needs, with the potential to improve the effectiveness of employee attendance management.